Designing an Educational Program Model Towards Furnishing Secondary School Students with Positive Attitudes for 'Peace Education' - Gülay Bedir; Mehmet Arslan (Informascope, 2014)
Lack of education seems to be the source of not only the increase in the frequency of undemocratic and violent events in a society, but also for many other troubles we have. One way to raise democratic individuals that a society needs is to train or educate them through such an educational program leading to the mastery of information, skills, abilities, and attitudes that would enhance being democratic. The purpose of this study is to draft a design of an educational program model that would enable secondary school students to develop values and attitudes towards peace education. The purpose of the peace education program is to furnish secondary school students with positive attitudes and values towards peace education.. Literature survey has revealed seven categories of values and attitudes regarding peace education. During the designing phase of the program, interviews were conducted with teachers, students, and school administrators in order to hold a needs analysis under the light of the literature feedback. Data obtained after needs analysis directed the preparation of learning outcomes (goals), content, educational settings, and evaluation parts concerning these values and attitudes. Values and attitudes identified in this study are: Values and attitudes regarding human rights (Personal rights, interpersonal rights, societal freedom and political rights), Values and attitudes concerning cooperation and solidarity, Values and attitudes about preservation of cultures, Values and attitudes individuals have for themselves and for others, Values and attitudes regarding international solidarity, Values and attitudes concerning the protection of environment, Values and attitudes about spirituality.